2021
DOI: 10.1039/d0na00787k
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable hyperbolic metamaterial perfect absorber

Abstract: Metamaterial (MM) perfect absorbers are realised over the various spectra from visible to microwave. Recently, different approaches have been explored to integrate tunability into the MM absorbers. Particularly, tuning has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…Instead of VO 2 , some other PCMs capable of reconfiguring their electrical properties at different crystalline states have also been demonstrated to effectively modulate the absorption performance of MAs. [28,30,131] For instance, Jeong et al reported a reconfigurable MA based on the PCM of germanium telluride (GeTe). [30] By applying temperature from 25 to 250 °C, the GeTe films located between the gap of a circular patch transited from an amorphous state with high resistance to a crystalline lowresistive state, resulting in the reconfigurability of the resonant frequency from 10.23 to 9.6 GHz, as displayed in Figure 5i.…”
Section: Phase-change Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead of VO 2 , some other PCMs capable of reconfiguring their electrical properties at different crystalline states have also been demonstrated to effectively modulate the absorption performance of MAs. [28,30,131] For instance, Jeong et al reported a reconfigurable MA based on the PCM of germanium telluride (GeTe). [30] By applying temperature from 25 to 250 °C, the GeTe films located between the gap of a circular patch transited from an amorphous state with high resistance to a crystalline lowresistive state, resulting in the reconfigurability of the resonant frequency from 10.23 to 9.6 GHz, as displayed in Figure 5i.…”
Section: Phase-change Materialsmentioning
confidence: 99%
“…Instead of VO 2 , some other PCMs capable of reconfiguring their electrical properties at different crystalline states have also been demonstrated to effectively modulate the absorption performance of MAs. [ 28,30,131 ] For instance, Jeong et al. reported a reconfigurable MA based on the PCM of germanium telluride (GeTe).…”
Section: Periodic Patterns For Tunable/reconfigurable Masmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Multilayers are the most common realization of HMMs. [12] Of special interest is the interaction of temperature with multilayer HMMs, either in wavelength-switchable temperature-actuated hyperlenses [13] and super absorbers [14] or in applications with high operating temperatures such as thermophotovoltaics, [15,16] hyperthermia therapy, [17,18] or radiative cooling. [19][20][21] However, one of the key challenges for all of these proposed applications is thermal stability.…”
mentioning
confidence: 99%